Sarcopenia related to neoadjuvant chemotherapy and perioperative outcomes in resected gastric cancer: a multi-institutional analysis - Mirkin, Katelin A.; Luke, Franklyn E.; Gangi, Alexandra; Pimiento, Jose M.; Jeong, Daniel; Hollenbeak, Christopher S.; Wong, Joyce (Journal of Gastrointestinal Oncology; Vol 8, No 3 (June 23, 2017): Journal of Gastrointestinal Oncology (Novel Biologics In Era of Precision Medicine)1, 2017)
Background: This study’s objective was to evaluate the change in sarcopenia score following neoadjuvant chemotherapy (NAC) and to correlate both sarcopenia and change in score with perioperative outcomes in patients with advanced resected gastric cancer. Methods: Multi-institutional analysis of patients with gastric cancer who underwent NAC and resection from 2000–2015 was performed. Demographic and perioperative data were included. Sarcopenia score was defined as CT measurement of total psoas muscle at L3, stratified by height (m). Sarcopenia was defined as a score